PERLINDUNGAN KONSUMEN TERHADAP TRANSAKSI JUAL BELI MELALUI MEDIA INTERNET (E-COMMERCE) - DAHLIA - (Universitas Slamet Riyadi, 2009)
Abstarct: Protection toward consumers in internet (E-commerce) transaction covers protection toward privacy, accuracy, property, and accessibility in digital signature. It is stated in clause 4 of UPPK. If a violation happens in the transaction, one can ask for a way out both in the court or out of court. Keywords: consumers’ protection, E-commerce